Estudio de prefactibilidad para la instalación de una planta de tratamiento de residuos de aparatos eléctricos y electrónicos (RAEE) - Liendo Casapino, Claudia Patricia (2022)
Nowadays, waste generation has increased to an alarming level and it is of major importance to treat them to minimize the risk that they represent both for the environment and for people's health. The focus of this research is directed at a type of waste that is not taken much into account, the waste from electrical and electronic equipment. Over the years, technology’s progress and the constant updates that arise from it have increased the waste generation to a great extent. Electrical and electronic devices are made up of a long list of materials, which with proper treatment can be recovered in the form of secondary raw material, but are also made up of some components, which are a very dangerous pollutant, for example the batteries. Therefore, it seeks to further investigate the recycling processes of these wastes and thereby recover the materials with which they are produced, forming a circular economy. The investigation will begin with a description of the objectives, the hypothesis that is proposed to be tested and the social, technological and economic justification of the project. The waste from electrical and electronic devices’ collecting process, their composition and the materials that can be rescue from them will also be described. In the second chapter, a market study will be achieved, in which information will be collected through primary sources, such as surveys and interviews or secondary sources, such as thesis seminars, magazines, newspapers, internet articles, and research studies from different national entities, for example “Ministerio del Ambiente” (MINAM). With this information, the amount of waste electrical and electronic equipment available in the country, the target market and the demand for the project can be defined. In the third and fourth chapter, the analysis of the optimal location and size of the plant will be carried out respectively. First, the Lima Metropolitan region and the constitutional province of Callao will be evaluated, with the micro-location factors that qualify as most relevant to the study, and tools such as the ranking of factors will be used to select the district where the recycling plant will be installed. On the other hand, the plant size required for the project will be calculated. In the fifth chapter, the engineering of the project will be explained. First, one of the existing technologies will be chosen for the development of operations within the plant. Then the waste collection and treatment activities will be described in detail, as well as the recycling processes for secondary raw materials and the machinery and equipment necessary to obtain them. On the other hand, the plant layout analysis will be carried out, which will include the environmental study, the maintenance and security plan within the plant and the distribution of the different areas within the proposed land. The next chapter will describe the constitution of the company and the main functions of the personnel that comprise it. In the seventh chapter, the evaluation of the profitability of the business is presented. This section will define the total contribution required for the project's investment, the costs and expenses that are necessary for the production, the income statement, the net cash flows, and the economic and financial indicators. In the next chapter, the social evaluation of the project will be presented. Finally, the conclusions and recommendations obtained from the study will be exposed, with which the validity of the hypothesis will be verified.